Mapping of a new autosomal dominant non-syndromic hearing loss locus (DFNA43) to chromosome 2p12. Issue 4 (1st April 2003) - Flex, E; Mangino, M; Mazzoli, M; Martini, A; Migliosi, V; Colosimo, A; Mingarelli, R; Pizzuti, A; Dallapiccola, B
Abstract : Hearing impairment (HI) is the most frequent sensory defect with wide genetic heterogeneity. Approximately 80% of genetic hearing loss is non-syndromic and 15–25% of exhibit autosomal dominant inheritance. We analysed an Italian three generation family in which non-syndromic hearing impairment is transmitted as an autosomal dominant trait. Onset of HI in all affected subjects occurred in the second decade of life, with subsequent gradual progression from moderate to profound loss. HI was bilateral and symmetrical, involving all frequencies. After exclusion of the known DFNA loci with markers from the Hereditary Hearing Loss Homepage (URL: http://dnalab-www.uia.ac.be/dnalab/hhh ), a genome wide scan was carried out using 358 highly informative microsatellite markers. Significant linkage (Zmax=4.21, θ=0) was obtained with chromosome 2p12 markers. The results were confirmed by multipoint analysis (Zmax=4.51), using the location score method. Haplotype analysis defined a 9.6 cM disease gene interval on chromosome 2 without overlap with the other identified loci. Fine mapping and identification of candidate genes are in progress.